High-toughness plastic film and preparation method thereof

By adopting a combined structure of cast polypropylene film layer and modified coating layer on the plastic film, the shortcomings of traditional plastic films in terms of toughness, slipperiness and antistatic properties are solved, and efficient packaging process and product quality are achieved. promote.

CN119431856APending Publication Date: 2025-02-14HEBEI TEDA NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821086.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Traditional plastic films have shortcomings in toughness, slippage and antistatic properties, which lead to prone to rupture and tear on automated packaging lines, affecting packaging efficiency and product quality.

Method used

The combined structure of cast polypropylene film layer and coating layer is adopted. The raw materials of the coating layer include polyacrylic acid, benzoyl peroxide, propylene oxide, polydimethylsiloxane and silane coupling agent KH-570. Corona treatment of polypropylene films and activated acrylic spray treatment are carried out through low-temperature plasma convection, and curing with ultraviolet light to form a highly tough plastic film.

Benefits of technology

It significantly improves the toughness, slippage and antistatic properties of plastic films, reduces cracking and tearing, improves packaging efficiency and product quality, and reduces preparation costs and environmental pollution risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431856A_ABST
    Figure CN119431856A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of plastic films, and particularly discloses a high-toughness plastic film and a preparation method thereof. The high-toughness plastic film is prepared from the following raw materials: polyacrylic acid, benzoyl peroxide, epoxypropane, polydimethylsiloxane, a silane coupling agent KH-570, a casting polypropylene film and activated acrylic acid. The high-toughness plastic film disclosed by the invention is high in toughness, good in smoothness and antistatic property, simple in preparation method and suitable for large-scale popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic films, and in particular to a high-toughness plastic film and a preparation method thereof. Background Art

[0002] As people's quality of life improves, their requirements for paper products are getting higher and higher, and correspondingly, the requirements for the outer packaging of such products are also getting higher and higher. In the past, due to the low demand for paper products and the relatively single variety, traditional paper product packaging generally only used low-grade paper boxes or ordinary polyethylene films. Now, with the rapid growth of demand for paper products, the demand for packaging materials is also growing rapidly. As a common packaging material, plastic film plays an important role in modern life. However, traditional plastic films have obvious deficiencies in toughness, smoothness and antistatic properties.

[0003] First of all, toughness refers to the ability of a material to absorb energy and resist rupture when subjected to external forces. In practical applications, plastic films often encounter various mechanical force challenges, such as stretching, impact, puncture, etc. Traditional plastic films, especially polyethylene films, have good ductility due to the linearity and regularity of their molecular structure, but their lack of toughness is particularly prominent under low temperature or high-speed stretching conditions. This brittle behavior limits the use of films in some applications that require high toughness. For example, on automated packaging lines, the film's lack of toughness can lead to rupture and tearing during the packaging process, affecting packaging efficiency and product quality.

[0004] Secondly, the performance of traditional plastic films in terms of slipperiness is often unsatisfactory. On high-speed packaging production lines, friction between films and between films and other objects can cause packaging speeds to slow down or even cause jamming. In addition, insufficient slipperiness of the film may also make it difficult to remove the packaged paper products from the packaging, affecting the consumer experience. In order to improve the slipperiness of traditional plastic films, it is usually necessary to add slip agents during the production process. However, the use of these additives may bring new problems, such as migration and precipitation of additives, which will not only reduce the transparency and printing quality of the film, but may also cause environmental pollution and food safety issues.

[0005] Finally, antistatic performance is an important indicator when plastic films are used in electronics, precision instruments, medical and health fields. The accumulation of static electricity may lead to dust adsorption, damage to electronic equipment, and even fire accidents. Although plastic film itself is a poor conductor of electricity, static charge will be generated on the surface of the film during actual use due to friction, contact separation and other effects. Traditional plastic films usually have a high resistivity due to the characteristics of their molecular structure, and it is difficult to dissipate static electricity quickly. This requires the addition of antistatic agents to improve the antistatic properties of the film. However, the addition and use of antistatic agents also have problems, such as insufficient durability of antistatic performance and migration of antistatic agents leading to decreased film performance. In addition, the use of antistatic agents may also increase production costs and the risk of environmental pollution. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for preparing a high-toughness plastic film.

[0007] A high-toughness plastic film, comprising a cast polypropylene film layer and a coating layer coated on the surface of the cast polypropylene film layer; The raw materials of the coating layer include, by weight: 1-2 parts of polyacrylic acid, 0.02-0.04 parts of benzoyl peroxide, 0.5-0.8 parts of propylene oxide, 1-2 parts of polydimethylsiloxane, 0.03-0.05 parts of silane coupling agent KH-570, and 1-2 parts of activated acrylic acid.

[0008] Preferably, the raw materials of activated acrylic acid include: 10-15 parts of acrylic acid and 0.2-0.4 parts of benzoyl peroxide, and the weight ratio of acrylic acid to benzoyl peroxide is 10-15:0.2-0.4.

[0009] Preferably, in the preparation process of activated acrylic acid, acrylic acid and benzoyl peroxide are dissolved in deionized water, stirred for 0.5-1h at a stirring speed of 300-500r / min, and vaporized in a vaporization chamber at a vaporization temperature of 150-160°C to obtain activated acrylic acid.

[0010] A method for preparing a high-toughness plastic film comprises the following steps: S1, dissolving polyacrylic acid in deionized water, adding benzoyl peroxide and stirring, adding propylene oxide in a constant temperature water bath, stirring, adjusting the pH value of the system to 7-7.5, and removing the solvent by evaporation with a rotary evaporator to obtain modified polyacrylic acid; S2, mixing modified polyacrylic acid and polydimethylsiloxane, adding silane coupling agent KH-570, stirring, standing in a constant temperature water bath, cooling, and obtaining a composite; S3, corona treatment of the cast polypropylene film by low-temperature plasma, placing it above the vaporization chamber and spraying activated acrylic acid, irradiating it with a high-pressure mercury lamp, and blowing it with hot air to obtain an activated cast polypropylene film; S4, mixing the compound and toluene, stirring, coating the compound and toluene on the surface of the activated cast polypropylene film by a coating machine, and curing the mixture by an ultraviolet curing device to obtain a high-toughness plastic film.

[0011] Preferably, in step S1, benzoyl peroxide is added and stirred at a stirring speed of 200-300 r / min.

[0012] Preferably, in step S1, the stirring time is 0.2-0.5h, and the stirring speed is 200-300r / min.

[0013] Preferably, in step S1, a hydrochloric acid solution with a concentration of 0.1-0.5 mol / L is used to adjust the pH value of the system to 7-7.5.

[0014] Preferably, in step S1, propylene oxide is added in a constant temperature water bath at 60-70° C., and the propylene oxide addition rate is 2%-3% per minute based on the total weight of propylene oxide.

[0015] Preferably, in step S2, the stirring time is 0.5-1h, and the stirring speed is 200-300r / min.

[0016] Preferably, in step S2, the temperature of the constant temperature water bath is 70-80° C., and the standing time of the constant temperature water bath is 2-3 hours.

[0017] Preferably, in step S3, the cast polypropylene film is subjected to corona treatment by low-temperature plasma for 5-10 minutes, the treatment power is 5-8kw, and the corona voltage is 380-400V.

[0018] Preferably, in step S3, hot air at 50-60° C. is used for blowing.

[0019] Preferably, in step S3, the irradiation treatment is performed by a high-pressure mercury lamp with a wavelength of 360-370 nm, the irradiation time is 10-20 min, and the irradiation power is 1-1.5 kw.

[0020] Preferably, in step S4, the activated cast polypropylene film is coated on its surface by a coating machine, with a coating thickness of 5-8 μm and a coating speed of 1-1.5 m / min.

[0021] Preferably, in step S4, the stirring time is 0.5-1h, and the stirring speed is 300-500r / min.

[0022] Preferably, in step S4, the UV light is cured by a UV curing device with an intensity of 80-90 mW / cm 2 , wavelength is 360-370nm, and curing speed is 1-1.5m / min.

[0023] Beneficial effects: Polyacrylic acid has excellent thermal stability, which enables it to maintain its performance in a variety of applications. The epoxy group is a highly reactive functional group that can undergo a ring-opening reaction with a variety of compounds to form a stable chemical bond. In the present invention, the carboxyl group in polyacrylic acid reacts with propylene oxide to form a stable epoxy group (-O-CH 2 -CH 2 -O-), compounded with activated cast polypropylene film, effectively improves the cohesion and toughness of the material, making it less likely to break and tear on the automated packaging line, thereby increasing packaging efficiency and product quality.

[0024] The epoxy groups of modified polyacrylic acid and the silicon-oxygen bonds in polydimethylsiloxane are further used to form stable CO-Si covalent bonds. This is a stable cross-linked network that can not only further improve the cohesion of the material and enhance the toughness of the plastic film, but also has good slipperiness and antistatic properties, and is not easy to migrate and precipitate, thus ensuring the transparency of the film and the printing quality. The composite of the invention has good fluidity and uniformity during coating, high adhesion strength on the surface of activated cast polypropylene film, and rapid solidification by initiating free radical polymerization reaction under ultraviolet light irradiation. The formed film has extremely high stability, which significantly improves production efficiency.

[0025] The high-toughness plastic film of the invention has high toughness, good smoothness and antistatic properties, can meet the market demand for such packaging materials, and has low preparation cost and simple preparation method, and is suitable for large-scale promotion and production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a comparison chart of tensile strength tests of the high-toughness plastic films obtained in Example 5 and Comparative Examples 1-2.

[0027] Figure 2 This is a comparison chart of the elongation at break test of the high-toughness plastic films obtained in Example 5 and Comparative Examples 1-2.

[0028] Figure 3 This is a comparison chart of the static friction coefficient test of the high-toughness plastic film obtained in Example 5 and Comparative Examples 1-2.

[0029] Figure 4 This is a comparison chart of the dynamic friction coefficient test of the high-toughness plastic film obtained in Example 5 and Comparative Examples 1-2.

[0030] Figure 5This is a comparison chart of surface resistivity tests of the high-toughness plastic films obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0031] The present invention will be further explained below in conjunction with specific embodiments.

[0032] Example 1 A method for preparing a high-toughness plastic film comprises the following steps: S1, dissolving 10g of polyacrylic acid in 50g of deionized water, adding 0.2g of benzoyl peroxide and stirring at a speed of 200r / min, adding 5g of propylene oxide in a 60°C constant temperature water bath, with the total weight of propylene oxide as the basis, the propylene oxide addition rate is 2% per minute, stirring for 0.2h, stirring at a speed of 200r / min, using a hydrochloric acid solution with a concentration of 0.1mol / L to adjust the pH value of the system to 7, and removing the solvent by evaporation on a rotary evaporator to obtain modified polyacrylic acid; S2, mixed modified polyacrylic acid and 10g polydimethylsiloxane, added 0.3g silane coupling agent KH-570, stirred for 0.5h at a stirring speed of 200r / min, placed in a constant temperature water bath at 70°C for 2h, cooled, and obtained a composite; S3, corona treatment of 180g cast polypropylene film for 5min by low-temperature plasma treatment machine, treatment power is 5kw, corona voltage is 380V, placed above the vaporization chamber and sprayed with 10g activated acrylic acid, irradiated by high-pressure mercury lamp with wavelength of 360nm, irradiation time is 10min, irradiation power is 1kw, purged with 50℃ hot air, to obtain activated cast polypropylene film; S4. Mix the composite and 50 g of toluene, stir for 0.5 h at a stirring speed of 300 r / min, coat the activated cast polypropylene film with a coating machine at a coating thickness of 5 μm and a coating speed of 1 m / min, and cure with a UV curing device at a UV light intensity of 80 mW / cm 2 , wavelength is 360nm, curing speed is 1m / min, and a high-toughness plastic film is obtained.

[0033] Preparation method of activated acrylic acid: dissolve 10g acrylic acid and 0.2g benzoyl peroxide in 200g deionized water, stir for 0.5h at a stirring speed of 300r / min, vaporize through a vaporization chamber at a vaporization temperature of 150°C to obtain activated acrylic acid.

[0034] Example 2 A method for preparing a high-toughness plastic film comprises the following steps: S1, dissolving 20g of polyacrylic acid in 80g of deionized water, adding 0.4g of benzoyl peroxide and stirring at a speed of 300r / min, adding 8g of propylene oxide in a 70°C constant temperature water bath, with the total weight of propylene oxide as the basis, the propylene oxide addition rate is 3% per minute, stirring for 0.5h, the stirring speed is 300r / min, using a hydrochloric acid solution with a concentration of 0.5mol / L to adjust the pH value of the system to 7.5, and removing the solvent by evaporation on a rotary evaporator to obtain modified polyacrylic acid; S2, mixed modified polyacrylic acid and 20g polydimethylsiloxane, added 0.5g silane coupling agent KH-570, stirred for 1h at a stirring speed of 300r / min, placed in a constant temperature water bath at 80°C for 3h, cooled, and obtained a composite; S3, corona treatment of 250g cast polypropylene film for 10min by low-temperature plasma treatment machine, treatment power is 8kw, corona voltage is 400V, placed above the vaporization chamber and sprayed with 20g activated acrylic acid, irradiated by high-pressure mercury lamp with wavelength of 370nm, irradiation time is 20min, irradiation power is 1.5kw, purged with 60℃ hot air, to obtain activated cast polypropylene film; S4, the composite material and 80g toluene were mixed and stirred for 1h at a stirring speed of 500r / min, and coated on the surface of the activated cast polypropylene film by a coating machine with a coating thickness of 8μm and a coating speed of 1.5m / min, and cured by a UV curing device with a UV light intensity of 90mW / cm 2 , wavelength is 370nm, curing speed is 1.5m / min, and a high-toughness plastic film is obtained.

[0035] Preparation method of activated acrylic acid: 15g acrylic acid and 0.4g benzoyl peroxide are dissolved in 300g deionized water, stirred for 1h at a stirring speed of 500r / min, and vaporized in a vaporization chamber at a vaporization temperature of 160°C to obtain activated acrylic acid.

[0036] Example 3 A method for preparing a high-toughness plastic film comprises the following steps: S1, dissolving 12g of polyacrylic acid in 60g of deionized water, adding 0.25g of benzoyl peroxide and stirring at a speed of 220r / min, adding 6g of propylene oxide in a 62°C constant temperature water bath, with the total weight of propylene oxide as the basis, the propylene oxide addition rate is 2.2% per minute, stirring for 0.3h, stirring at a speed of 220r / min, using a hydrochloric acid solution with a concentration of 0.2mol / L to adjust the system pH value to 7.1, and removing the solvent by evaporation on a rotary evaporator to obtain modified polyacrylic acid; S2, mixed modified polyacrylic acid and 12g polydimethylsiloxane, added 0.35g silane coupling agent KH-570, stirred for 0.6h at a stirring speed of 220r / min, placed in a constant temperature water bath at 72°C for 2.2h, cooled, and obtained a composite; S3, corona treatment of 200g cast polypropylene film for 6min by low-temperature plasma treatment machine, treatment power is 6kw, corona voltage is 385V, placed above the vaporization chamber and sprayed with 12g activated acrylic acid, irradiated by high-pressure mercury lamp with wavelength of 362nm, irradiation time is 12min, irradiation power is 1.1kw, purged with 52℃ hot air, to obtain activated cast polypropylene film; S4, the composite material and 60g toluene were mixed and stirred for 0.6h at a stirring speed of 350r / min, and coated on the surface of the activated cast polypropylene film by a coating machine with a coating thickness of 6μm and a coating speed of 1.1m / min, and cured by a UV curing device with a UV light intensity of 82mW / cm 2 , wavelength is 362nm, curing speed is 1.1m / min, and a high-toughness plastic film is obtained.

[0037] Preparation method of activated acrylic acid: dissolve 11g acrylic acid and 0.25g benzoyl peroxide in 220g deionized water, stir for 0.6h, the stirring speed is 350r / min, and vaporize through a vaporization chamber at a vaporization temperature of 152°C to obtain activated acrylic acid.

[0038] Example 4 A method for preparing a high-toughness plastic film comprises the following steps: S1, dissolving 18g of polyacrylic acid in 70g of deionized water, adding 0.35g of benzoyl peroxide and stirring at a speed of 280r / min, adding 7g of propylene oxide in a 68°C constant temperature water bath, with the total weight of propylene oxide as the basis, the propylene oxide addition rate is 2.8% per minute, stirring for 0.4h, stirring at a speed of 280r / min, using a hydrochloric acid solution with a concentration of 0.4mol / L to adjust the pH value of the system to 7.4, and removing the solvent by evaporation on a rotary evaporator to obtain modified polyacrylic acid; S2, mixed modified polyacrylic acid and 18g polydimethylsiloxane, added 0.45g of silane coupling agent KH-570, stirred for 0.9h at a stirring speed of 280r / min, placed in a constant temperature water bath at 78°C for 2.8h, cooled, and obtained a composite; S3, corona treatment of 230g cast polypropylene film by low-temperature plasma treatment machine for 9min, treatment power of 7kw, corona voltage of 395V, placed above the vaporization chamber and sprayed with 18g activated acrylic acid, irradiated by high-pressure mercury lamp with wavelength of 368nm, irradiation time of 18min, irradiation power of 1.4kw, purged with 58℃ hot air, to obtain activated cast polypropylene film; S4, the composite material and 70g toluene were mixed and stirred for 0.9h at a stirring speed of 450r / min, and coated on the surface of the activated cast polypropylene film by a coating machine with a coating thickness of 7μm and a coating speed of 1.4m / min, and cured by a UV curing device with a UV light intensity of 88mW / cm 2 , wavelength is 368nm, curing speed is 1.4m / min, and a high-toughness plastic film is obtained.

[0039] Preparation method of activated acrylic acid: 14g acrylic acid and 0.35g benzoyl peroxide are dissolved in 280g deionized water, stirred for 0.9h at a stirring speed of 450r / min, and vaporized in a vaporization chamber at a vaporization temperature of 158°C to obtain activated acrylic acid.

[0040] Example 5 A method for preparing a high-toughness plastic film comprises the following steps: S1, dissolving 15g of polyacrylic acid in 65g of deionized water, adding 0.3g of benzoyl peroxide and stirring at a speed of 250r / min, adding 6.5g of propylene oxide in a 65°C constant temperature water bath, with the total weight of propylene oxide as the basis, the propylene oxide addition rate is 2.5% per minute, stirring for 0.35h, stirring at a speed of 250r / min, using a hydrochloric acid solution with a concentration of 0.3mol / L to adjust the pH value of the system to 7.2, and removing the solvent by evaporation on a rotary evaporator to obtain modified polyacrylic acid; S2, mixed modified polyacrylic acid and 15g polydimethylsiloxane, added 0.4g silane coupling agent KH-570, stirred for 0.7h at a stirring speed of 250r / min, placed in a constant temperature water bath at 75°C for 2.5h, cooled, and obtained a composite; S3, corona treatment of 220g cast polypropylene film for 7min by low-temperature plasma treatment machine, treatment power is 6.5kw, corona voltage is 390V, placed above the vaporization chamber and sprayed with 15g activated acrylic acid, irradiated by high-pressure mercury lamp with wavelength of 365nm, irradiation time is 15min, irradiation power is 1.2kw, purged with 55℃ hot air, to obtain activated cast polypropylene film; S4, the composite material and 65g toluene were mixed and stirred for 0.7h at a stirring speed of 400r / min, and coated on the surface of the activated cast polypropylene film by a coating machine with a coating thickness of 6.5μm and a coating speed of 1.2m / min, and cured by a UV curing device with a UV light intensity of 85mW / cm 2 , wavelength is 35nm, curing speed is 1.2m / min, and a high-toughness plastic film is obtained.

[0041] Preparation method of activated acrylic acid: 12g acrylic acid and 0.3g benzoyl peroxide are dissolved in 250g deionized water, stirred for 0.7h at a stirring speed of 400r / min, and vaporized in a vaporization chamber at a vaporization temperature of 155°C to obtain activated acrylic acid.

[0042] Comparative Example 1 220g cast polypropylene film.

[0043] Comparative Example 2 A method for preparing a high-toughness plastic film comprises the following steps: S1. Mix 15 g of polyacrylic acid and 15 g of polydimethylsiloxane, add 0.4 g of silane coupling agent KH-570, stir for 0.7 h at a stirring speed of 250 r / min, place in a constant temperature water bath at 75° C. for 2.5 h, and cool to obtain a composite; S2, corona treatment of 220g cast polypropylene film for 7min by low-temperature plasma treatment machine, treatment power is 6.5kw, corona voltage is 390V, placed above the vaporization chamber and sprayed with 15g activated acrylic acid, irradiated by high-pressure mercury lamp with wavelength of 365nm, irradiation time is 15min, irradiation power is 1.2kw, purged with 55℃ hot air, to obtain activated cast polypropylene film; S3, the composite material and 65g toluene were mixed and stirred for 0.7h at a stirring speed of 400r / min, and coated on the surface of the activated cast polypropylene film by a coating machine with a coating thickness of 6.5μm and a coating speed of 1.2m / min, and cured by a UV curing device with a UV light intensity of 85mW / cm 2 , wavelength is 35nm, curing speed is 1.2m / min, and a high-toughness plastic film is obtained.

[0044] Preparation method of activated acrylic acid: 12g acrylic acid and 0.3g benzoyl peroxide are dissolved in 250g deionized water, stirred for 0.7h at a stirring speed of 400r / min, and vaporized in a vaporization chamber at a vaporization temperature of 155°C to obtain activated acrylic acid.

[0045] Test Example 1 The tensile strength and elongation at break of the high-toughness plastic films obtained in Example 5 and Comparative Examples 1-2 were tested as follows: According to ASTM D882 standard, 4 groups of specimens of the same size were cut from the plastic films of Example 5 and Comparative Examples 1-2, respectively, and recorded as Group 1, Group 2, Group 3, and Group 4; the edges of the specimens were ensured to be flat without notches or cracks; both ends of the specimens were clamped in the fixture of the testing machine using an electronic universal material testing machine to ensure that the clamping force was uniform and would not cause the specimens to break at the fixture, the tensile speed of the testing machine was set to 50 mm / min, the test was started, the testing machine stretched the specimens uniformly until the specimens broke, and the maximum force and elongation at break were recorded.

[0046] Use the following formula to calculate: Tensile strength

[0047] Among them, F max is the maximum force when the specimen breaks (N), A 原始 is the original cross-sectional area of ​​the specimen (mm²) Use the following formula to calculate: Elongation at break ) , Among them, L 断裂 is the length of the specimen when it breaks (mm), L 原始 is the original gauge length of the specimen (mm).

[0048] Depend on Figure 1 , Figure 2 It can be seen that the high-toughness plastic film in Example 5 exhibits the best toughness. This is because the carboxyl groups in polyacrylic acid react with propylene oxide to form stable epoxy groups (-O-CH 2 -CH 2 -O-), the epoxy group can not only form a stable CO-Si covalent bond with the silicon-oxygen bond in the polydimethylsiloxane to enhance the toughness of the plastic film, but also be compounded with the activated cast polypropylene film to further improve the cohesion and toughness of the material. In Comparative Example 2, although no modified polyacrylic acid is added, the polydimethylsiloxane itself also has the performance of improving the toughness of the cast polypropylene film material, so although its toughness is not as good as that of Example 5, it is also better than that of Comparative Example 1.

[0049] Test Example 2 The high-toughness plastic films obtained in Example 5 and Comparative Examples 1-2 were tested for friction coefficient, as follows: According to GB / T 10006-2021 standard, 4 groups of film samples of the same size were cut from the plastic films of Example 5 and Comparative Examples 1-2, respectively, and recorded as Group 1, Group 2, Group 3, and Group 4; the cut film samples were fixed on the platform of a friction coefficient tester (MXD-02 model), and the test speed was set to 100 mm / min. After the test is completed, the instrument will automatically calculate the static friction coefficient and the dynamic friction coefficient and record the data.

[0050] Depend on Figure 3 , Figure 4 It can be seen that the high-toughness plastic film in Example 5 exhibits the best slipperiness, which is due to the fact that the epoxy group of the modified polyacrylic acid can form a stable CO-Si covalent bond with the silicon-oxygen bond in the polydimethylsiloxane, which is a stable cross-linked network that can greatly enhance the slipperiness of the material. At the same time, through the coating process, the compound has good fluidity and uniformity on the surface of the activated cast polypropylene film, further improving the slipperiness of the film surface. Comparative Example 1 did not go through the above treatment process, so its slipperiness is the worst.

[0051] Test Example 3 The surface resistivity of the high-toughness plastic film obtained in Example 5 and Comparative Example 2 was tested as follows: According to GB / T 1410 standard, 4 groups of samples of the same size are cut from the plastic films of Example 5 and Comparative Examples 1-2, respectively, and are recorded as Group 1, Group 2, Group 3, and Group 4; all tests should be carried out at room temperature, the temperature is controlled at 23±2°C, and the humidity is controlled at 50%±5%; the cut film samples are laid flat on the test platform of the resistivity meter, and the test voltage of the surface resistivity meter (such as GB / T 1410-2006 plastic film resistivity meter) is set to 500V. After the test is completed, the instrument will automatically calculate the surface resistivity and record the data.

[0052] Depend on Figure 5 It can be seen that the high-toughness plastic film in Example 5 exhibits the best antistatic performance, which is because the epoxy group of the modified polyacrylic acid can form a stable CO-Si covalent bond with the silicon-oxygen bond in the polydimethylsiloxane, which is a stable cross-linked network that can greatly enhance the antistatic performance of the material. Comparative Example 1 did not go through the above treatment process, so its antistatic performance was the worst.

[0053] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high-toughness plastic film, characterized in that: It comprises a cast polypropylene film layer and a coating layer coated on the surface of the cast polypropylene film layer; The raw materials of the coating layer include, by weight: 1-2 parts of polyacrylic acid, 0.02-0.04 parts of benzoyl peroxide, 0.5-0.8 parts of propylene oxide, 1-2 parts of polydimethylsiloxane, 0.03-0.05 parts of silane coupling agent KH-570, and 1-2 parts of activated acrylic acid.

2. A high-toughness plastic film according to claim 1, characterized in that: The raw materials of activated acrylic acid include acrylic acid and benzoyl peroxide, and the weight ratio of acrylic acid to benzoyl peroxide is 10-15:0.2-0.

4.

3. A high-toughness plastic film according to claim 2, characterized in that: In the preparation process of activated acrylic acid, acrylic acid and benzoyl peroxide are dissolved in deionized water, stirred for 0.5-1h at a stirring speed of 300-500r / min, and vaporized in a vaporization chamber at a vaporization temperature of 150-160°C to obtain activated acrylic acid.

4. A method for preparing a high-toughness plastic film according to any one of claims 1 to 3, characterized in that: The steps include: S1, dissolving polyacrylic acid in deionized water, adding benzoyl peroxide and stirring, adding propylene oxide in a constant temperature water bath, stirring, adjusting the pH value of the system to 7-7.5, and removing the solvent by evaporation with a rotary evaporator to obtain modified polyacrylic acid; S2, mixing modified polyacrylic acid and polydimethylsiloxane, adding silane coupling agent KH-570, stirring, standing in a constant temperature water bath, cooling, and obtaining a composite; S3, corona treatment of the cast polypropylene film by low-temperature plasma, placing it above the vaporization chamber and spraying activated acrylic acid, irradiating it with a high-pressure mercury lamp, and blowing it with hot air to obtain an activated cast polypropylene film; S4, mixing the compound and toluene, stirring, coating the compound and toluene on the surface of the activated cast polypropylene film by a coating machine, and curing the mixture by an ultraviolet curing device to obtain a high-toughness plastic film.

5. The method for preparing a high-toughness plastic film according to claim 4, characterized in that: In the step S1, benzoyl peroxide is added and stirred at a stirring speed of 200-300 r / min.

6. The method for preparing a high-toughness plastic film according to claim 4, characterized in that: In the step S1, propylene oxide is added in a constant temperature water bath at 60-70° C., and the propylene oxide addition rate is 2%-3% per minute based on the total weight of propylene oxide.

7. The method for preparing a high-toughness plastic film according to claim 4, characterized in that: In the step S3, the cast polypropylene film is subjected to corona treatment by low-temperature plasma for 5-10 minutes, the treatment power is 5-8kw, and the corona voltage is 380-400V.

8. The method for preparing a high-toughness plastic film according to claim 4, characterized in that: In the step S3, the material is irradiated by a high-pressure mercury lamp with a wavelength of 360-370 nm, the irradiation time is 10-20 min, and the irradiation power is 1-1.5 kw.

9. The method for preparing a high-toughness plastic film according to claim 4, characterized in that: In the step S4, the activated cast polypropylene film is coated on its surface by a coating machine, with a coating thickness of 5-8 μm and a coating speed of 1-1.5 m / min.

10. The method for preparing a high-toughness plastic film according to claim 4, characterized in that: In step S4, the UV light is cured by a UV curing device with an intensity of 80-90 mW / cm 2 , wavelength is 360-370nm, and curing speed is 1-1.5m / min.